3+-3(-2h+6)=

Simple and best practice solution for 3+-3(-2h+6)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3+-3(-2h+6)= equation:


Simplifying
3 + -3(-2h + 6) = 0

Reorder the terms:
3 + -3(6 + -2h) = 0
3 + (6 * -3 + -2h * -3) = 0
3 + (-18 + 6h) = 0

Combine like terms: 3 + -18 = -15
-15 + 6h = 0

Solving
-15 + 6h = 0

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '15' to each side of the equation.
-15 + 15 + 6h = 0 + 15

Combine like terms: -15 + 15 = 0
0 + 6h = 0 + 15
6h = 0 + 15

Combine like terms: 0 + 15 = 15
6h = 15

Divide each side by '6'.
h = 2.5

Simplifying
h = 2.5

See similar equations:

| 104=4(2-4x) | | x+41=70 | | 6[5-8(-4)]+12=x | | 6(-1+x)=-54 | | 891.25=7.5x+4.75y | | 0.80x+0.05(4-x)=0.10(-88) | | 11-3n=9n+2 | | 157=113-u | | 2(x+19)=x+29 | | 4+4x=x | | -9t+-7(-6+-10)= | | 2(x+9)=x+29 | | y-47=-41 | | x-40=30 | | 22=9n-(-4) | | 6(n-4)=-54 | | 4(m-2)=1 | | 13=6+6 | | log[5]3+log[5]t+log[5](t+4)=log[5]63 | | -2(10x-1)=-48-10x | | 2(x+2)=3x-8 | | 16-7x=-61 | | 10m+9n+4m= | | -4+6(-6+10h)-4h= | | 1.8d+3=2(.9d-1.5) | | A(x)=2x+8x+14 | | 3m+7=7m+6 | | -12+5k=15-45 | | (9x-6)+(3x+8)= | | 7(2+9g)= | | 7.50x+4.75x=891.25 | | 6(3+5y)+(y-8)=13 |

Equations solver categories